Official Toponyms and Their Dialectal Variants: The Influence of the Dialectal Forms of Moroccan Place Names - Malak, Alasli (Wydawnictwo Uniwersytetu Jagiellońskiego, 2025)
Morocco displays strong multilingualism where several languages coexist: Standard Arabic, Berber (Amazigh), French, Spanish, and Moroccan Arabic (Darija) – the vernacular language. Nonetheless, following independence, the country’s ideological choices in terms of cultural policy pushed for the Arabization of toponyms. To provide high-quality geographic information, place names should be accurate and identifiable in the field not only by the inhabitants themselves but also by the visitors. Place names are rather close to everyday life and thus used mostly in their vernacular form, denoting phonetic or semantic alterations. Various research has shown the interrelation between dialectology and onomastics, hence the importance of considering dialects in the study of place names. This study aims to investigate whether examining and considering the dialectal variants is essential. It seeks to provide a comprehensive toponymic data set of Morocco, where the motivation is better identification of the place in question by adhering to the correct usage in both written and spoken practice. The onymic items were collected from native speakers of the geographical varieties and oral tradition. The differences in the linguistic features are analyzed, and follow-up investigations will seek to examine whether any discrepancy between the official and the vernacular form of toponym will be observed.